The role of spiritual leadership in improving employee performance - Mahfud, Imam (Priviet Social Sciences Journal, 2023)
This study explores the role of spiritual leadership in enhancing employee performance. The purpose of this research is to understand how spiritual leadership contributes and influences the improvement of employee performance. The research methodology employed is a literature study using a descriptive approach. Data collection techniques involve gathering information from books, journals, websites, and other sources. The findings of this research indicate that to achieve competitive advantage, organizations require various supporting factors, and one of these supporters is spiritual leadership, which aims to build high commitment across all organizational components in achieving common goals. Performance can be understood differently depending on the individuals involved in organizational performance considerations, requiring knowledge of personality or behavior related to the accountable field and the ability to quantify the results. The conclusion drawn from this research is that religious physiological performance (prophetic work ethic) is measured by the use of natural resources, expertise, technology, and capital in an Islamic manner. Religious psychological performance is measured by the utilization of health, social interactions, recognition, and self-improvement in an Islamic way. Spiritual performance is measured by the level of trust, honesty, trustworthiness, and sincere intentions in work and production orientation in an Islamic manner. Spiritual leadership is leadership that brings the worldly dimension to the spiritual (divine) dimension, addressing the fundamental needs between leaders and followers in the organization's sustainability towards shared spirituality, leading to increased commitment and productivity for the organization. The importance of management creating spirituality in the workplace lies in its ability to stimulate creativity, which in turn enhances competitiveness. In fulfilling their roles, employee performance cannot operate in isolation but is linked to the leadership role and the level of motivation obtained by the company. Therefore, leaders in a company should understand the importance of spiritual leadership that can influence employee performance in the company.